Đặt: \(A=\left(x-3\right)\left(x+3\right)+2\left(2x+1\right)^2\)
=> \(A=x^2-9+2\left(4x^2+4x+1\right)\)
=> \(A=x^2-9+8x^2+8x+2\)
=> \(A=9x^2+8x-7\)
=> \(A=\left(3x+\frac{4}{3}\right)^2-\frac{79}{9}\)
Có: \(\left(3x+\frac{4}{3}\right)^2\ge0\forall x\Rightarrow\left(3x+\frac{4}{3}\right)^2-\frac{79}{9}\ge-\frac{79}{9}\)
=> \(A\ge-\frac{79}{9}\)
DẤU "=" XẢY RA <=> \(\left(3x+\frac{4}{3}\right)^2=0\)
<=> \(x=-\frac{4}{9}\)
Vậy A min = \(-\frac{79}{9}\) <=> \(x=-\frac{4}{9}\)
( x - 3 )( x + 3 ) + 2( 2x + 1 )2
= x2 - 9 + 2( 4x2 + 4x + 1 )
= x2 - 9 + 8x2 + 8x + 2
= 9x2 + 8x - 7
= 9x2 + 8x + 16/9 - 79/9
= ( 3x + 4/3 )2 - 79/9
\(\left(3x+\frac{4}{3}\right)^2\ge0\forall x\Rightarrow\left(3x+\frac{4}{3}\right)^2-\frac{79}{9}\ge-\frac{79}{9}\)
Dấu " = " xảy ra <=> 3x + 4/3 = 0 => x = -4/9
=> GTNN của biểu thức = -79/9 <=> x = -4/9